2018
DOI: 10.1002/jcb.27633
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Overexpression of microRNA‐590‐3p promotes the proliferation of and inhibits the apoptosis of myocardial cells through inhibition of the NF‐κB signaling pathway by binding to RIPK1

Abstract: Ischemic heart disease is widely considered as a major health threat, which causes a high number of deaths every year worldwide. Much evidence has shown that oxidative stress (OS) is implicated in the pathogenesis of ischemiareperfusion injury (IRI). This study aims to evaluate the effect of miR-590-3p on the OS of IRI mice through the nuclear factor kappa-B (NF-κB) signaling pathway by targeting receptor-interacting protein kinase 1 (RIPK1). IRI mouse models were established for extracting myocardial tissues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…Considering the important role of the NF-κB signaling pathway in inflammatory response (35), the activity of the NF-κB signaling pathway was assessed and it was confirmed that NEAT1/miR-590-3p could regulate the activity of the NF-κB signaling pathway. Similar to previous studies, the regulatory role of miR-590-3p and the NF-κB signaling pathway has also been confirmed in our study (24)(25). However, studies have also shown that miR-590-3p inhibited the activity of the NF-κB signaling pathway in peritoneal macrophages (24) and mice primary cardiomyocytes (25).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Considering the important role of the NF-κB signaling pathway in inflammatory response (35), the activity of the NF-κB signaling pathway was assessed and it was confirmed that NEAT1/miR-590-3p could regulate the activity of the NF-κB signaling pathway. Similar to previous studies, the regulatory role of miR-590-3p and the NF-κB signaling pathway has also been confirmed in our study (24)(25). However, studies have also shown that miR-590-3p inhibited the activity of the NF-κB signaling pathway in peritoneal macrophages (24) and mice primary cardiomyocytes (25).…”
Section: Discussionsupporting
confidence: 91%
“…Zhao et al (24), reported that miR-590-3p could target the NF-κB signaling pathway to regulate the inflammation of myocarditis. Another study suggested that miR-590-3p could relieve oxidative stress in ischemia-reperfusion injury mice models by regulating the NF-κB signaling pathway (25). Recent studies have shown that the NF-κB signaling pathway is closely associated with cell apoptosis and involved in the transcriptional regulation of various apoptosis-related genes, playing a decisive role in the process of apoptosis (26,27).…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that lncRNAs exert their effects through interacting with miRNAs to regulate downstream targets. Online prediction software indicates that several miRNAs are the potential targets of PART‐1, and miR‐590‐3p was selected as the target for examination, due to the regulatory effects of miR‐590‐3p on apoptosis in different types of cells . Consequently, we have constructed two luciferase reporter vectors, one containing wide‐type miR‐590‐3p–binding site and the other containing the mutant one (Figure A).…”
Section: Resultsmentioning
confidence: 99%
“…24 In our study, we found that the activity and expression of caspase-1 and IL-1b were significantly increased in HG-treated HRMECs and clinical vitreous samples, suggesting that pyroptosis is involved in the pathogenesis of DR. Increasing evidence has demonstrated that miRNAs function as effective biomarkers or therapeutic targets, 25 and many miRNAs have been shown to have important roles in DR progression. 26,27 In our study, we initially investigated the role in DR of miR-590-3p, which is an inflammation-related miRNA 16,18,28 that may participate in the progression of pyroptosis. Our results indicated that the miR-590-3p inhibitor induced pyroptosis, which is consistent with the HG-induced condition.…”
Section: Discussionmentioning
confidence: 99%
“…14 Studies have indicated that miRNAs have critical roles in the pathogenesis of DR by mediating cell proliferation, migration, and death. 15 miR-590-3p has been shown to promote proliferation in ischemia-reperfusion injury by inhibiting the NF-jB pathway, 16 which has an active role in inflammatory responses. 17 Moreover, miR-590-3p is associated with the accumulation of IL-18 in osteoblasts 18 and bioinformatic analysis predicted that it binds to the 3 0 -UTR of NLRP1 and NOX4 (miRDB; available in the public domain at http:// mirdb.org/).…”
mentioning
confidence: 99%